2020
DOI: 10.26452/ijrps.v11ispl4.4604
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and GC MS analysis of methanolic extract of Abelmoschus moschatus

Abstract: The study was designed to evaluate the phytoconstituents present in the methanolic extract of aerial parts of Abelmoschus moschatus. The qualitative phytochemical screening of different extracts of aerial parts revealed the presence of some bioactive compounds. GC – MS analysis was performed using Shimadzu Gas chromatography-mass spectroscopy (Model Number: QP2010S) instrument. GC-MS detection of phytoconstituents was done by computer evaluation of mass spectra of samples through National Institute Standard an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…such as isoflavones, lectins, saponins and phenolic compounds, which are characterized by their cytotoxic activity and can be used in the treatment and prevention of cancer [359]. By way of example, Souza et al [360] evaluated the cytotoxicity of flavonoid isolated from Macroptilium martii and observed a lower antiproliferative activity (20.96 %) against HeLa cancer cell lines than that determined in the present study.…”
Section: Based On Results Ofcontrasting
confidence: 43%
“…such as isoflavones, lectins, saponins and phenolic compounds, which are characterized by their cytotoxic activity and can be used in the treatment and prevention of cancer [359]. By way of example, Souza et al [360] evaluated the cytotoxicity of flavonoid isolated from Macroptilium martii and observed a lower antiproliferative activity (20.96 %) against HeLa cancer cell lines than that determined in the present study.…”
Section: Based On Results Ofcontrasting
confidence: 43%
“…Furthermore, the fatty acid components of pentadecanoic acid, hexadecanoic acid, and octadecenoic acid methyl ester were also found by GCMS analysis. Those compounds were proven to possess antimicrobial activity by previous studies; beta-sitosterol was observed in C. rotundus [19], and 3, 4-Altrosan was found in Ziziphus mauritiana fruit extract [20], and isoquinoline was separated from Chelidonium majus extract. Plant extracts are chosen for the treatment of urinary tract infections (UTIs) in pregnant women due to their safety, potential avoidance of antibiotics, compatibility with traditional medicine, rich bioactive compounds, broad antimicrobial spectrum, accessibility, affordability, and guidance.…”
Section: Resultsmentioning
confidence: 93%
“…moschatus Medik seed induced hepatotoxicity. (Christina et al, 2012) reported on the phytochemical investigation and diuretic activity of A. moschatus Medik. Camciuc et al (1998) analyzed the volatile components in okra seed coat.…”
Section: Introductionmentioning
confidence: 99%